The Correlation between Students’ Motivation and Students’ English Speaking Skill at English Education Department Universitas Muhammadiyah Yogyakarta - Muhammad Kenang Maulana (PBI 15 UMY 055, 2015)
*55 Speaking skill becomes one of the English skills that students should master. It has a lot of factors that could influence students to improve their speaking skill. Those are clustering, redundancy, reduced forms, performance variables, colloquial language, rate of delivery, stress, rhythm and intonation, interaction, and affective factors. The affective factor here includes motivation. This study only focused on the correlation between students’ motivation and their English speaking skill. This was a quantitative study which involved 50 students of English Education Department batch 2011 at Universitas Muhammadiyah Yogyakarta. Questionnaire was used to get data for Independent variable (students’ motivation) and students’ speaking score was used to obtain the data for dependent variable (Students’ speaking skill). Through data analysis using SPSS version 22, this study found that the student motivation was fair (83.35 of 103) and the students speaking ability was good (42.1 of 53.34). The next finding was about the correlation between motivation and speaking ability of the student. The finding indicates a positive and significant correlation between students’ motivation and students’ speaking skill (r = 0.38 and p = 0.007). This indicates that the correlation is low or weak yet significant. Thus, the alternative hypothesis is accepted because there is a significant positive relationship between students’ motivation and students’ speaking skill at English Education Department.